Hands-on Activities through Gardening: Building Twenty-First Century Skills for Lifelong Learning - Acharya, Kamal Prasad; Gyawali, Kalpana; Upadhyaya, Indra Raj (Interdisciplinary Research in Education, 2024)
This article explores the contribution of students’ garden-based activities to develop 21st century skills in the public schools in Nepal. It employed a participatory action research methodology, the research consisted of three purposively sampled intervention schools. The intervention involves the cultivation of flowers and vegetables, thus making gardening as part of the teaching and learning. Conversations, interviews and field reflections were the methods of collection of data, based on it, themes were made. The results indicate that the school garden enhances critical thinking, creativity, collaboration and problem solving skills as required in twenty first century education. In addition, students expressed the gardening activity as something that is related to what they have been learning and they appreciated it as a great learning platform. It encourages creative thinking, environmental sustainability and competence for lifelong learning.